Pengaruh Konsentrasi dan Frekuensi Pupuk Pelengkap Cair Terhadap Aklimatisasi Anggrek Hitam - kurniawati, atika; Listiawati,MP, Ir. Agustina; Budi, MMA, Ir. Setia (Jurnal Sains Mahasiswa Pertanian, 2019)
The Effect of Concentration and Frequency of Complementary Liquid Fertilizers on Black Orchid Acclimatization  Atika Kurniawati(1), Agustina Listiawati (2), Setia Budi (2)1)Students of Agriculture Faculty(2)Lecturer of Agriculture Faculty, Tanjungpura University PontianakEmail: atikakurniawati55@gmail.com ABSTRACT  Acclimatization of orchids requires nutrition enough to support its growth. The provision of complementary liquid fertilizer with concentration right thing to do, because it can influence whether or not good growth seeds orchids. The frequency of the fertilizer needed to gain proper seeds optimal. This study aims to find the best combination of concentration and frequency of complementary liquid fertilizer Grow Quick S against acclimatization of black orchids. This research was conducted in the shade house of Green Villa, Faculty of Agriculture, Tanjungpura University, Pontianak. This study used a field experimental method with Split Plot Design, in which 2 frequency levels were put as main plots (main plot) which were f1 = once every 2 days, f2 = 3 days and 4 levels of concentration as subplots (sub plot) which were k1 = 1 ml/l, k2 = 2 ml/l, k3 = 3 ml/l, k4 = 4 ml/l. Each treatment consisted of 3 replications and each treatment consisted of 5 plant samples constitute to 120 plant samples. The variables observed in this study were increase in leaf length (cm), increase in number of leaves (strands), root length (cm), number of roots (strands) and number of shoots (shoots). Based on the results of the study it can be concluded that the provision of various types of concentrations and frequencies of complementary liquid fertilizer gives the same response on all variables, for the effectiveness of the use of complementary liquid fertilizer is a concentration of 1 ml/l and with the frequency every 3 days application. Keywords: Acclimatization, Black Orchid, Frequency, Concentration,      Complementary Liquid Fertilizer